Subtitling Strategies of Main Characters’ Expressive Utterances in the Little Mermaid (2023) - Rafi Galung Tangguh Saputra; Nadia Gitya Yulianita; Raden Pujo Handoyo (Program Studi Diploma Tiga Bahasa Inggris Fakultas Ilmu Budaya Unsoed, 2024)
This research delves into the subtitling strategies of expressive utterances in “The Little Mermaid (2023)”, employing a descriptive qualitative method for analyzing 40 instances of expressive utterances. The subtitling strategies identified encompass transfer (52.50%), condensation (15.00%), deletion and paraphrase (10.00% each), expansion (7.50%), and transcription (5.00%). The transfer strategy, being the most frequently used, serves as a crucial tool in enhancing the clarity of expressive utterances. The relationship between expressive and strategic types lies in the translator's deliberate selection of subtitling strategies to convey nuances and emotions inherent in each expressive type. This suggests a strategic alignment between the nature of the expressive utterance and the chosen subtitling technique. The findings emphasize the translator's nuanced decision-making process in conveying emotions effectively in subtitles. This research's unique focus on a specific film and comprehensive analysis of subtitling strategies to the understanding of film subtitle translation